Essays on entrepreneurship in a geographical context - Wolf, Christian (2019)
This thesis is a portfolio of three papers illuminating entrepreneurship through a geographical lens, particularly focusing on the entrepreneurial ecosystem, The first essay develops a theoretical model on the role of geography in crowdfunding preferences. The model is embedded in a theoretical review of literature on trends towards re-regionalization, or re-localization, in a globalized world. The model also accommodates for prominent examples of crowdfunding that attracted supporters irrespective of geography, developing that branch of the model on a discussion of literature on the passionate pursuit of special interests and herding within special interest groups globally. The second essay explores crowdfunding in the context of sub-Saharan Africa, especially the opportunities and challenges of crowdfunding. Microfinance, which has traditionally played an important role in African entrepreneurial development, is complemented with the opportunities provided by crowdfunding. Particular emphasis is given to cultural aspects surrounding crowdfunding, linking this relatively new phenomenon to longstanding African cultural traditions, such as harambee in Kenyan culture. Ongoing trends surrounding crowdfunding are identified, such as the rise of mobile payments, highlighting the potential of crowdfunding in sub-Saharan Africa. The third essay explores transnational acceleration. Transnational accelerator programs are a particular form of acceleration, offering startups fast-track access to different geographical locations. Focusing on innovation-driven entrepreneurship, this study explores the purposefully selected case of Building Global Innovators, which is a transnational accelerator based jointly in Portugal and Massachusetts. This study explores the extent of financial resources that the transnational accelerator program consumes in terms of its operating expenses in the context of the overall performance of the transnational accelerator program. Applying qualitative research, it this essay also explores the core value-added that a transnational accelerator provides to the startups it hosts.